JOINT OPTIMIZATION OF TOPOLOGY AND SIZE BASED ON MODAL ANALYSIS OF 750 POWER HEAD GEARBOX (MT) - LUO QingYi; MEI Qi; HU XiaoBing; LI-HE YuQiu (Jixie qiangdu, 2022)
In view of the uneven mass distribution and the excessive weight of the power head gearbox bodies, and the first-order natural frequency is close to the excitation frequency generated by the second-stage gear transmission. The Genesis module in the Ansys Workbench simulation platform was used to analyze the modal topology of the gearbox. Based on the size to be optimized obtained from the topology optimization, the gearbox body was optimized by the target drive optimization tool. Without affecting the strength and rigidity of the gearbox body, the mass was reduced by 12.9%, and the first-order natural frequency was increased by 10.9%, which achieved the dual purpose of reducing weight and increasing the first-order natural frequency. The research results have practical guiding significance for saving manufacturing costs and improving product performance.